Design of modular grid and graphic design multimedia edition "Pet" - Комарова, Дина Владимировна; Бизюк, Андрей Валерьевич (Eastern-European Journal of Enterprise Technologies, 2012)
The results of the development of interactive multimedia training application "Pet." are given. During the development of modular grid and graphic design applications were established and analysis of existing methods use different types of modular networks in the development of multimedia applications was also carried out